Sex disparities and the risk of urolithiasis: a large cross-sectional study. (31st December 2022) - Xu, Jin-Zhou; Li, Cong; Xia, Qi-Dong; Lu, Jun-Lin; Wan, Zheng-Ce; Hu, Liu; Lv, Yong-Man; Lei, Xiao-Mei; Guan, Wei; Xun, Yang; Wang, Shao-Gang
Abstract: Background: Urolithiasis is one of the most common diseases in urology, with a lifetime prevalence of 14% and is more prevalent in males compared to females. We designed to explore sex disparities in the Chinese population to provide evidence for prevention measures and mechanisms of stone formation. Materials and methods: A total of 98232 Chinese individuals who had undergone a comprehensive examination in 2017 were included. Fully adjusted odds ratios for kidney stones were measured using restricted cubic splines. Multiple imputations was applied for missing values. Propensity score matching was utilised for sensitivity analysis. Results: Among the 98232 included participants, 42762 participants (43.53%) were females and 55470 participants (56.47%) were males. Patients' factors might cast an influence on the development of kidney stone disease distinctly between the two genders. A risk factor for one gender might have no effect on the other gender. The risk for urolithiasis in females continuously rises as ageing, while for males the risk presents a trend to ascend until the age of around 53 and then descend. Conclusions: Patients' factors might influence the development of kidney stones distinctly between the two genders. As age grew, the risk to develop kidney stones in females continuously ascended, while the risk in males presented a trend to ascend and then descend, which was presumably related to the weakening of the androgen signals. Key messages: We found that patients' factors might cast an influence on the development of kidney stone disease distinctly between the two sexes. The association between age and urolithiasis presents distinct trends in the two sexes The results will provide evidence to explore the mechanisms underlying such differences can cast light on potential therapeutic targets and promote the development of tailored therapy strategies in prospect.